Pengaruh Filsafat Pendidikan Terhadap Strategi Pembelajaran dalam Pendidikan Teknologi Kejuruan - Dermawan, Andri; Syaifullah, Lasyatta; Jalinus, Nizwardi (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2021)
Philosophy is a comprehensive truth that is often contested with the truth of science which is relative in nature. This article discusses the influence of the philosophy of education on learning strategies on the Education Technology of Teaching. (PTK). The philosophy of education is the one used in the study of educational problems. Philosophy will determine where our students want to be carried. The philosophy is a tool of values that leads and guides towards the achievement of educational goals. Therefore, the philosophy followed by a particular nation or group of people or by individuals (in this case Teachers) will greatly influence the educational objectives to be achieved. The application of educational philosophy in PTK not only enhances the technical aspects but also builds individuals who have ethical integrity, interpersonal skills and readiness to face the dynamics of global industry. In this case there is the influence of the philosophy of education on learning strategies in the education of professional technology